1901 Mich. Pub. Acts 154, § 24, pt. 11 - (:unkn) unknown (My University, 1901)
Local Acts, No. 344, tit.7, § 24, pt. 11: To regulate, restrain and prohibit the buying, carrying and selling gunpowder, fire crackers [sic] or fireworks manufactured and prepared therefrom, or other combustible materials, the exhibition of fireworks and the discharge of firearms, and lights in barns, stables and other buildings, and to restrain the making of bonfires in streets, yards and public grounds[.]
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER